Zwitterionic Polymer Coating of Sulfur Dioxide‐Releasing Nanosystem Augments Tumor Accumulation and Treatment Efficacy. Issue 5 (28th January 2020) - Yao, Xianxian; Ma, Shuangping; Peng, Shaojun; Zhou, Gaoxin; Xie, Ruihong; Jiang, Qin; Guo, Shengdi; He, Qianjun; Yang, Wuli
Abstract: Multiple drug resistance (MDR) exhibited by cancer cells and low intratumor accumulation of chemotherapeutics are the main obstacles in cancer chemotherapy. Herein, the preparation of a redox‐responsive sulfur dioxide (SO2 )‐releasing nanosystem, with high SO2 ‐loading capacity, aimed at improving the treatment efficacy of cancers exhibiting MDR is described. The multifunctional nanomedicine (MON‐DN@PCBMA‐DOX) is designed and constructed by coating mesoporous organosilica nanoparticles with a zwitterionic polymer, poly(carboxybetaine methacrylate) (PCBMA), which can concurrently load SO2 prodrug molecules (DN, 2, 4‐dinitrobenzenesulfonylchloride) and chemotherapeutics (DOX, doxorubicin). The generated SO2 molecules can sensitize cells to chemotherapy and overcome the MDR by downregulating the expression of P‐glycoprotein. Furthermore, the PCBMA coating prolongs the blood circulation time of the inner core, leading to an increased intratumor accumulation of the nanomedicine. Owing to the prolonged blood circulation, enhanced tumor accumulation, and SO2 sensitization of cells to chemotherapy, the nanomedicine exhibits excellent tumor suppression with a tumor inhibition rate of 94.8%, and might provide a new platform for cancer therapy. Abstract : A redox‐responsive sulfur dioxide‐releasing nanosystem with long circulation time is developed by coating mesoporous organosilica nanoparticles with a zwitterionic polymer. The generated SO2 molecules can overcome multiple drug resistance. With the property of long circulation time, the functional nanosystem exhibits excellent tumor suppression functionality, which may provide a new platform for cancer therapy.